2021
DOI: 10.1007/s13197-021-05119-z
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa extract with high content of flavan 3-ols, procyanidins and methylxanthines

Abstract: The health benefits of cocoa depend on the flavan 3-ols, procyanidins, and methylxanthines, which decrease from the early stages of cocoa bean processing. The objective of this research was to obtain a cocoa extract high in these compounds with (-)-epicatechin as the primary reference. An evaluation of two pretreatments of cocoa beans with a control after harvesting was made: A (untreated/control), B (Frozen), and C (Polyphenol oxidase inhibition), all followed by dehydration at 45 °C until obtaining a cocoa p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…In cocoas from Peru, some authors reported ranges of 57.4–76.0 and 10.6–20.8 mg/g of theobromine and caffeine, respectively, with T/C ratios > 3 in all cases [ 67 ]. Similar results have been shown by other authors in cocoas from different regions of South America, with T/C ratios higher than 2 in all cases [ 33 , 51 , 52 ]. Overall, the present results are in line with those already published.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In cocoas from Peru, some authors reported ranges of 57.4–76.0 and 10.6–20.8 mg/g of theobromine and caffeine, respectively, with T/C ratios > 3 in all cases [ 67 ]. Similar results have been shown by other authors in cocoas from different regions of South America, with T/C ratios higher than 2 in all cases [ 33 , 51 , 52 ]. Overall, the present results are in line with those already published.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, the TPC values for non-alkalized cocoas were in line with those reported by Miller et al [ 12 ] (from 45.3 to 60.2 mg GAE/g), Samaniego et al [ 32 ] (from 33.6–71.7 mg GAE/g) for different cocoa powders, and Kobori et al [ 50 ] for a cocoa powder from Ghana (62.3 mg epicatechin equivalents/g). Analyzed cocoa powder 1 from Venezuela had a TPC of 34.4 mg GAE/g d.w; this is in the same range of magnitude as the results reported in cocoas from other regions of south America, with values that ranged from 44–202 mg GAE/g in cocoa beans from Colombia [ 33 , 51 , 52 ] and from 33.6–71.7 mg GAE/g in cocoa beans from Equator [ 32 ].…”
Section: Resultssupporting
confidence: 66%
“…Our TPC in cocoa by-products was higher than those reported in these extracts. When compared with the values of cocoa beans from Colombia (44–202 mg GAE/g DW), we are below these values even though this study is on whole beans and not on by-products [ 47 , 48 , 49 ]. The same occurs when we compare our values with the TPC of cocoa beans from Ecuador (33.6–71.7 mg GAE/g DW) [ 5 ].…”
Section: Resultsmentioning
confidence: 60%
“…Recently, scientific literature has highlighted the significance of discovering alternative anti-cancer agents from natural sources. Cocoa, a rich source of high-quality polyphenols including catechins (29%-38% of total polyphenols), anthocyanin (4% of total polyphenol), and proanthocyanins (58%-65% of total polyphenols), has been extensively studied for its anti-cancer properties with promising results (Acosta-Otálvaro et al, 2022;Maskarinec, 2009). However, a comprehensive isolating method is required to identify the lead anti-cancer agent from the phytochemical matrix (Manzoor et al, 2019).…”
Section: Discussionmentioning
confidence: 99%